Distinct EGFR Mutation Pattern in Patients With Non-Small Cell Lung Cancer in Xuanwei Region of China: A Systematic Review and Meta-Analysis - Lv, Li; Liu, Zhichao; Liu, Yang; Zhang, Wenhui; Jiang, Lifeng; Li, Tingting; Lu, Xinyan; Lei, Xuefen; Liang, Wenhua; Lin, Jie (Frontiers in Oncology, 2020)
Background: In Xuanwei region of China, the lung cancer incidence and mortality are among the highest in China attributed to severe air pollution generated by combustion of smoky coal. No study has yet comprehensively evaluated the prevalence of epidermal growth factor receptor (EGFR) mutation characteristics in patients with non-small cell lung cancer (NSCLC) in Xuanwei. This meta-analysis was designed to analyze the EGFR mutation pattern in NSCLC patients in Xuanwei region of Yunnan Province in China. Methods: Electronic databases were comprehensively searched and relevant literatures were retrieved. The odds ratio (OR) for EGFR mutations between Xuanwei region and non-Xuanwei region was calculated, and the absolute incidence of EGFR mutations in Xuanwei was pooled by mutation subtype. Results: Seven studies involving 1,355 patients with NSCLC from Yunnan Province (442 in Xuanwei and 913 in other region) were included. The EGFR mutation rate ranged between 30.19% and 55.56%. Higher uncommon EGFR mutations (OR: 5.69, 95%CI: 2.23-14.49, P<0.001) and lower common EGFR mutations (OR: 0.18, 95%CI: 0.07-0.45, P<0.001) were found in Xuanwei region, compared with non-Xuanwei region. Specifically, the uncommon EGFR mutation rate was 59.50% and common EGFR mutation rate was 40.50% in Xuanwei. The mutation incidence of exon 18 G719X (OR: 3.21, 95%CI: 1.48-6.97, P=0.003), exon 20 S768I (OR: 6.44; 95%CI: 2.66-15.60; P<0.001), and exon 18 G719X + 20 S768I (OR: 6.55; 95%CI: 1.92-22.33; P=0.003) in Xuanwei were significantly higher, while the frequency of 19 deletion (OR: 0.28, 95%CI: 0.11-0.77, P<0.001) and 21 L858R mutation (OR: 0.51, 95%CI: 0.31-0.84, P=0.007) were lower. Conclusions: The results highlight the distinct EGFR mutation spectrum of NSCLC patients in Xuanwei region compared with other regions, with higher uncommon mutations but lower common mutations. The distinct Xuanwei featured genetic variations provide a unique model to further study carcinogenesis of lung cancer.